Literature and the Making of the World Cosmopolitan Texts, Vernacular Practices - Helgesson, Stefan; Bodin, Helena; Alling, Annika Mörte (Cosmopolitan-Vernacular Dynamics in World Literatures, 2021)
This open access book positions itself at the intersection of world literature studies, literary anthropology and philosophical critiques of 'world' and 'globe' concepts. Doing so, it investigates how literature imagines and shapes worlds for its readers through linguistically specific cosmopolitan-vernacular dynamics, both at the level of textual engagement and on a material level of textual production and circulation. Moving from textual analyses in Part One - 'Worlds in Texts' - to combined analyses of texts, media and agents in the literary field in Part Two - 'Texts in Worlds' - the concerns of these nine chapters range from multilingualism, genre and style to material forms such as the little magazine or the scrapbook archive and finally to activities such as travel (as a writing profession) and literary promotion. With this focus on practice - which geographically engages with Constantinople, China, Russia, western Europe, North America, southern Africa and India - contributors demonstrate methodologically how world literature studies can bring the empirically specific detail to bear on global modes of analysis. It is precisely through such a dual optic that the world-making capacity of literature becomes apparent.